Morfogénesis de la fase sexual del helecho Lophosoria quadripinnata var. contracta (Lophosoriaceae) - Mendoza, Aniceto (1997)
The development and morphology of the gametophytes of the fern L. quadripinnata var. contracta are described from material collected in Robinson Crusoe Island (Juan Fernandez Archipelago, Chile). The spores were sown in Thompson medium (25 Petri dishes). Spore donnancy range was 1.5-20 days. germination pattero is Cyatheatype and the prothallial development Adiantum-type. The gametangia are typical of the leptosporangiate feros. This plant is monoecious. Sporophytes appeared after tbree months of culture. The two varieties differ in spore size, prothallus shape and number of antheridial ceUs.